2019
DOI: 10.2147/cmar.s213690
|View full text |Cite|
|
Sign up to set email alerts
|

<p>Long Noncoding RNA GAS5 Acts As A Tumor Suppressor In Laryngeal Squamous Cell Carcinoma Via miR-21</p>

Abstract: PurposeLong noncoding RNAs (lncRNAs) have been identified as an important class of noncoding RNAs that are deeply involved in multiple biological processes in tumorigenesis. This study is to investigate the critical roles and biological function of lncRNA growth arrest-specific 5 (GAS5) in tumorigenesis of laryngeal squamous cell carcinoma (LSCC).Patients and methodsA total of 59 samples of LSCC and paired adjacent tissue, as well as corresponding clinicopathological information were collected. GAS5 expression… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 39 publications
(44 reference statements)
4
18
0
Order By: Relevance
“…miR-21 can downregulate the Cdc25A, change the negative regulation of the G1/S phase of the cell cycle, and involve in DNA damage repair G2/M check the 19 point [31]. Numerous researches have shown that LncRNA GAS5 acts as a tumor suppressor in many types of malignancies by regulating the miR-21 [32][33][34][35]. In our research, we found overexpression of GAS5 reduced the resistance of drug and increased the apoptosis of gastric cancer cells.…”
Section: Discussionsupporting
confidence: 50%
“…miR-21 can downregulate the Cdc25A, change the negative regulation of the G1/S phase of the cell cycle, and involve in DNA damage repair G2/M check the 19 point [31]. Numerous researches have shown that LncRNA GAS5 acts as a tumor suppressor in many types of malignancies by regulating the miR-21 [32][33][34][35]. In our research, we found overexpression of GAS5 reduced the resistance of drug and increased the apoptosis of gastric cancer cells.…”
Section: Discussionsupporting
confidence: 50%
“…30,31 It is worth noting that GAS5 is provably down-regulated in various cancers and has the potential to be a tumor inhibitor. [32][33][34] With one accord, our results proved the inhibition of GAS5 expression in PCa tissues and cells.…”
Section: Discussionsupporting
confidence: 54%
“…In gastric cancer, lncRNA MT1JP regulated the expression of FBXW7 through competitively binding with miR-92a-3p, and played a role in inhibiting cell proliferation, migration, invasion and promoting cell apoptosis 50 . MiR-21 sponged by GAS5 has been reported in OSCC, hepatocellular carcinoma, laryngeal squamous cell carcinoma and ovarian cancer 13,[51][52][53] . In our study, we verified the same mechanism in CC cells.…”
Section: Discussionmentioning
confidence: 98%